CARE MAP FOR PATIENTS UNDER NUCLEAR MEDICINE PROCEDURES - Fernández Sola, Cayetano; Granero Molina, José; Aguilera Manrique, Gabriel (Investigación y Educación en Enfermería, 2009)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective: the development of a tool that provides the systematic, registration and care continuity in the nuclear medicine services. Methodology: this research was developed during 2004 as a result of the creation of the Nuclear Medicine Service in the Torrecárdenas Hospital, in Almeria, Spain. A nursing problem review was undertaken from the data that captured in the bibliography review and clinical practice. It was carried through consent techniques, a language standarization and its codification following the NANDA, NOC and NIC taxonomies. Starting from an initial valuation for focus basic needs, it described nursing diagnoses, complications and the associated interventions to the nursing diagnose and the collaboration problems. Finally, the evaluation and the care continuity report were established. Results: tables with data for the initial evaluation were compiled of the main nursing diagnoses (Deficient knowledge, Fear, Breast-feeding Interruption, and Injury Risk) related to the hoped results, expressed according to NOC taxonomy (Knowledge: Procedure, Fear Self-control; Breast-feeding: Weaning and Risk Control) and the nursing intervention (teaching: procedure, nervous tension decrease, breast-feeding suppression, environmental management: security,etc.); as well as the intervention associated to the collaboration problems. Conclusion: this care map provides the work using a nursing process. It also helps to register in a easy way the interventions made to patients with nuclear medicine procedure.